Some factors affecting the feeding ecology and socio-biology of the samango monkey, cercopithecus albogularis schwarzi roberts, 1931 - Skinner, J.D. (John Dawson), 1932- (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 1980.